Unwarranted Purchase of Multi Vitamin Syrup at Higher Rates in Chhattisgarh - CAG of India (CAG of India)
Unwarranted purchase of Multivitamin syrup at higher rates by placing purchase orders on backdate violating Government instructions resulted in loss to the State Government.